THE EFFECTIVENESS OF USING PICTURED STORY TO UPGRADE STUDENTS VOCABULARY - Wahibah Wahibah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2016)
The objective of the research was to find out the effectiveness of using pictured story to upgrade vocabulary at the first year student at SMP Negeri 3 Sabbang. The method of this research was pre-experimental method and this research was the second year students of first year at SMP Negeri 3 Sabbang. The researcher took 30 students to represent the total number of population. Pictured story is significantly effective in teaching narrative text to upgrade students vocabulary of the first year students of SMPN 3 Sabbang. It can be proved by the result of students in pre test and post test. Pictured story is an appropriate method to teach English in junior high school because the students have experiences that almost the same with the story. So, they are curious to know the meaning of the story. Furthermore, it can make classroom situation attractive, interesting and make the students enjoy getting the material, also the students relax during the treatment process.